Recycling of mushroom compost wheat straw in the diet of feedlot calves with two physical forms - Hassan Fazaeli; Housain Shafyee-Varzeneh; Ali Farahpoor; Abdolossein Moayyer (International Journal of Recycling of Organic Waste in Agriculture)
Background This experiment was conducted to study the effect of diet contained mushroom spent wheat straw (MSWS) remained from Agaricus bisporus mushroom as well as the physical form of the diet on the performance of the feedlot calves. At the end of mushroom harvesting period, MSWS was collected from production room and the casing soil was removed from the whole compost, then it was sun dried and sampled for chemical analysis. In a completely randomized design, 24 Holsteins male calves with initial weight of 201.9 ± 1.0 kg were allocated to four experimental diets containing (1) standard pellet diet; (2) pellet diet with 15 % MSWS; (3) standard mash diet and (4) mash diet contained 15 % of MSWS. Results Average daily gain was 1,261, 1,146, 1,093 and 830 g; dry matter intake was 7.91, 6.51, 8.07 and 8.15 kg/ animal/day and feed conversion ratio was 6.32, 5.69, 7.39 and 8.76 for the diets respectively that were significantly different (P.05) among the treatments. Results of slaughtering observations showed that no differences could be detected in carcass and internal organs of the calves that received different diets. Conclusions The spent compost straw could be included up to 15 % in finishing calve diet in the pellet form.